GAMBARAN PROSES REHABILITASI PADA REMAJA PENGGUNA NARKOBA DI BADAN NARKOTIKA NASIONAL (BNN) KABUPATEN SUMBAWA - wanda utanty; Ayuning Atmasari (Fakultas Psikologi Universitas Teknologi Sumbawa, 2024)
Abuse is always increasing every year. Narcotics abuse is not only carried out by adults, but there are also many teenagers who fall into this forbidden item, which ultimately results in death. Therefore, the rehabilitation process needs to be introduced further, the hope is that it can reduce the victims of narcotics abusers. The purpose of this study is to determine the process of implementing rehabilitation for perpetrators of narcotics abuse crimes carried out by the Sumbawa Regency National Narcotics Agency (BNN). This research uses a qualitative method with a descriptive approach. Qualitative research intends to understand the phenomenon of what is experienced by the research subject, for example the perpetrator, perception, motivation, action, holistically by means of decryption in the form of words and discussions, in a special natural context by utilizing various scientific methods. The subjects of this research are counselors and drug users undergoing rehabilitation at the Sumbawa Regency National Narcotics Agency (BNN) Pratama Clinic. Data collection using interview, observation and documentation techniques. The number of informants in this research amounted to 1 person. The results of the research obtained from the Sumbawa Regency National Narcotics Agency (BNN) are that in carrying out the rehabilitation process for perpetrators of drug abuse crimes there are several stages of rehabilitation including: 1) Screaning intake/assessment stage, 2) Detoxification Stage, 3) Individual Counseling Stage 4) Family Counseling Stage, 5) Post Rehabilitation. Keywords: Rehabilitation, Adolescent Drug Users